People’s views towards Gunung Palung National Park, West Kalimantan, Indonesia - JAJAT SUDRAJAT; SITI SAWERAH; NIA PERMATASARI; ANITA SUHARYANI; AMELDALIA KARMONI; GUSTI Z. ANSHARI; DADANG WARDHANA; DICKO ROSSANDA (Biodiversitas Journal of Biological Diversity, 2018)
Sudrajat J, Sawerah S, Permatasari N, Suharyani A, Karmoni A, Anshari GZ, Wardhana D, Rossanda D. 2018. People’s views towards Gunung Palung National Park, West Kalimantan, Indonesia. Biodiversitas 19: 1138-1146. It is a common belief that the management of national park prevents local communities from accessing the park and using the park resources. Illegal logging and other unwanted encroachments to the park become a big problem, as national park authority has a limited capacity to monitor the whole park. This research aimed to study how local communities viewed Gunung Palung National Park, which is located in Ketapang and Kayong Utara District, West Kalimantan Province, Indonesia. A total of 91 respondents from seven villages were interviewed. In general, about 70% of respondents viewed the importance of economic benefits, resulting from limited access to traditional gardens in the use zone of the park and the supply of clean water. Approximately 67% of these respondents viewed the protection of natural resources in the park was not important. This view was possibly due to their little knowledge of the park management and the use of zoning system in the park. It was reported that park officers have some activities, but the collaboration and relationship between park officers and local communities need more time to mature. It seems that the poor and the youth tend to exploit more and put higher pressures on the park than the elderly groups.